Prevalence of progressive multifocal leukoencephalopathy (PML) in adults and children with systemic lupus erythematosus. Issue 1 (7th June 2020) - Kapoor, Teja; Mahadeshwar, Pooja; Hui-Yuen, Joyce; Quinnies, Kayla; Tatonetti, Nicholas; Gartshteyn, Yevgeniya; Guo, Cathy; Geraldino-Pardilla, Laura; Askanase, Anca D
Abstract : Objective: To define the risk of progressive multifocal leukoencephalopathy (PML) in SLE. Methods: This is a retrospective observational study to evaluate PML cases in patients with SLE admitted to two large academic hospitals. Using electronic medical record (EMR) data, International Classification of Diseases (ICD) codes identified PML cases among patients with SLE, rheumatoid arthritis (RA) (controls), had renal transplant and with HIV. Medication exposure was reviewed. Results: A total of 5409 Columbia University Medical Center (CUMC) patients and 2046 Northwell Health patients were identified using one ICD code for SLE. Of 7455 patients, three had an ICD code for PML. On EMR review, however, PML was substantiated in only one fatal SLE case with significant immunosuppressant use and severe lymphopenia (<0.5 cells x 10 9 /L); one patient was evaluated for PML but cerebrospinal fluid (CSF) was negative for JC virus and improved with treatment of central nervous system (CNS) lupus. EMR data were very limited for the third patient and diagnosis could not be confirmed. None of the 13 342 patients with RA ICD codes had PML. Of the 5409 patients with an SLE ICD code at CUMC, 212 also had a renal transplant ICD code, and 83 had concomitant HIV/AIDS. Based on inpatient pharmacy records of 5409 hospitalised patients at CUMC, 59.2% were treated with steroids, and 16.09% with immunosuppressants (7.76% mycophenolate, 3.42% cyclophosphamide, 2.88% azathioprine and 2.03% rituximab). No patients with paediatric SLE (pSLE) (n=538) had PML. The combined prevalence of PML in hospitalised patients with SLE at the two hospitals was 13–27/100 000 patients. Conclusion: Among 7455 adult patients with SLE ICD codes, there were two PML cases, with only one confirmed case associated with severe lymphopenia and immunosuppressants, corresponding to a prevalence of 13–27 per 100 000 patients. No PML cases in pSLE were found. A high index of suspicion in patients with SLE and CNS manifestations is required for the prompt diagnosis of PML.